Biosynthesis of natural colorant by Talaromyces amestolkiae: Mycelium accumulation and colorant formation in incubator shaker and in bioreactor - de Oliveira, Fernanda [UNESP]; Ferreira, Laura Carmona [UNESP]; Neto, Álvaro Baptista [UNESP]; Simas Teixeira, Maria Francisca; de Carvalho Santos Ebinuma, Valéria [UNESP] (Elsevier, 2020)
Fungi bioproducts have recently become commercially important to the food and pharmaceutical industry. However, different structural forms exhibited by filamentous fungi throughout their life cycles are often a bottleneck for productivity in many industrial processes. In this work, the relationship among mycelium accumulation, morphology, and colorant production was evaluated. Experiments were performed in an incubator shaker and in a stirred-tank bioreactor. First, a series of nitrogen sources and pure vitamins were investigated as additives to the monosodium glutamate-glucose medium in order to improve Talaromyces amestolkiae red colorant production in the incubator shaker. MSG and pH played an important role in generating stress, which affected cell growth and colorants production. The colorant synthesis seems to be is triggered under metabolic stress. Next, the effects of starter culture composition (MSG-glucose and nitrogen complex starter media) and airflow (2.0 and 8.0 Lmin−1) were investigated in the bioreactor. After 120 h of cultivation in the bioreactor, a maximum red colorant production of 9.33 UA500nm, 72.38 % glucose consumption, and 4.53 g L-1 biomass concentration were achieved under complex nitrogen as starter medium at 8 Lmin−1. Growth remained at moderate level, probably affected by the synergistic effect of MSG and pH as stress factors. Moreover, pellets formation favored suitable oxygenation of the culture broth leading to the best consumption of the carbon source.
Keywords: Bioreactor; Cell morphology; Natural colorants; Scaling-up; Talaromyces amestolkiae